STRATEGI GURU TILAWAH DALAM MENGAJARKAN TILAWAH AL-QUR’ᾹN PADA REMAJA DI DUSUN TELUK DURIAN DESA SEPADU KECAMATAN TELUK KERAMAT - Nuryati Nuryati (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
This research was conducted because the researchers wanted to know how the recitation teachers taught the recitations of the Qur'an to teenagers, so that many generations of Qur'āni were born. This study aims to clearly describe; 1) The strategy of recitation teachers in teaching al-Qur'ān recitations to adolescents in Teluk Durian Hamlet, Sepadu Village, Teluk Keramat District in 2021. 2) Al-Qur'ān recitation learning system for adolescents in Teluk Durian Hamlet, Sepadu Village, Teluk Keramat District in 2021 This study uses a qualitative approach and the type of descriptive research. Data collection techniques using interviews, observation, documentation. The technical analysis of the data used is data reduction, data display, and conclusions. The results of the study concluded that: 1) There are 3 strategies used by recitation teachers in teaching al-Qur'ān recitations to adolescents, namely musyafahah, step by step and assignments. The musyafahah strategy is used to teach material about sound and the law of recitation. While the step by step strategy is used to teach the material about the recitation of the Qur'an. Assignment strategies are used to practice together and are often carried out so that students can master the entirety of the recitation of the Qur'an. 2) The learning system used by the recitation teacher is a classical, semi-classical, individual classical, and individual reading-listening learning system. classical and semi-classical, namely learning systems that are carried out in large groups and small groups, individual classical and individual reading-listening, namely learning systems that are carried out together and alternately and others are listening.